Antibody responses elicited by mRNA vaccination in firefighters persist six months and correlate inversely with age and directly with BMI. Issue 1 (January 2023) - Holtkamp, Caroline; Schöler, Lara; Anastasiou, Olympia E.; Brune, Bastian; Fessmann, Kai; Elsner, Carina; Möhlendick, Birte; Čiučiulkaitė, Ieva; Dudda, Marcel; Trilling, Mirko; Dittmer, Ulf; Spors, Jörg; et al.
Abstract: Knowledge regarding the sustainability of immune responses after COVID-19 vaccination is important, e.g., to decide whom and when to booster. Thus, we analyzed antibody titers in firefighters six months after vaccination with the mRNA-based vaccine Comirnaty. SARS-CoV-2 spike-binding antibodies (bAb) were quantified and compared to peak responses determined in healthcare workers (HCW). For the firefighters, neutralizing antibodies (nAb) were also analyzed. Six months after the second vaccine dose, all analyzed firefighters had detectable bAb, and 91% exhibited nAb titers above 1:16. However, actual titers six months after vaccination were over 12-fold lower than in the HCW control group four weeks after vaccination. bAb and nAb responses showed a significant correlation, and age correlated inversely with antibody responses. Unexpectedly, participants with a body mass index over 25 had higher neutralization titers after six months. All participants with very low neutralization titers were offered booster vaccination. The booster vaccination improved the extent and sustainability of antibody responses. Highlights: All participants showed detectable antibody responses six months after vaccination. Age correlated inversely with antibody responses. Neutralizing antibody titers appear to correlate positively with BMI. Booster vaccination increased longevity of antibody responses.